Needs Analysis of Training Web Exe CMS (Content Management System) and Arduino “Two In One” For Physics Teacher - Umi Pratiwi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2019)
Most of physics teachers in Purworejo Regency use conventional teaching media. This is due to the lack of understanding and information about the latest It-based teaching media. They need new breakthroughs and methods to improve the quality of physics learning, especially those related to the development of teaching media. Therefore CMS (Content Management System) web exe and Arduino-based training needs analysis are conducted for Purworejo Regency physics teachers. This effort are tested by research descriptions are by giving questionnaires to respondents. The results showed that Purworejo district physics teachers needed continuous and periodic training with guided monitoring and needed training related to the latest IT-based teaching media such as e learning and microcontroller-based teaching media such as Arduino.